Solution to an open problem in gracefulness of arbitrary supersubdivisions of graphs - Kathiresan K.M.; Sumathi R. (Utilitas Mathematica, 2011)
In this paper, we answer one question posed by Sethuraman and Selvaraju[8]. " Are there any graphs different from paths whose arbitrary supersubdivisions are graceful?" The answer is affirmative; for the family of two new graphs whose arbitrary supersubdivisions are graceful.